Tangata Whenua, People Born of the Land: From Corporate Dispossession and Repossession to Severance and Reconnection - Scobie, Matthew (Journal of business ethics, 2026)
This paper explores Indigenous resistance to corporate dispossession in both a historical and contemporary context. Using two case studies of corporate dispossession of Ngāi Tahu land and resources in Aotearoa New Zealand, we advance understanding of dispossession and resistance through Indigenous critique. Although over 170 years apart, these cases are linked together by a singular Indigenous experience and demonstrate the recursive (self-referential and self-reinforcing) logic of both dispossession and Indigenous resistance. We utilise the concepts of ‘severance’ as a more locally appropriate term for dispossession, and ‘reconnection’ as a more locally appropriate term for repossession. These concepts also have broader use for exploring the relationship between capitalism and its outside. Indigenous critique offers valuable insights beyond particular Indigenous contexts, and Indigenous struggles provide an alternative power base to defend shared rights and reconnect these shared rights with shared responsibilities. Indigenous critique thus offers a glimpse of possible futures.